Ancient hybridization patterns between bighorn and thinhorn sheep - Santos, Sarah H. D.; Peery, Rhiannon M.; Miller, Joshua M.; Dao, Anh; Lyu, Feng-Hua; Li, Xin; Li, Meng-Hua; Coltman, David W. (My University, 2021)
Whole-genome sequencing has advanced the study of species evolution, including the detection of genealogical discordant events such as ancient hybridization and incomplete lineage sorting (ILS). The evolutionary history of bighorn (Ovis canadensis) and thinhorn (Ovis dalli) sheep present an ideal system to investigate evolutionary discordance due to their recent and rapid radiation and putative secondary contact between bighorn and thinhorn sheep subspecies, specifically the dark pelage Stone sheep (O. dalli stonei) and predominately white Dall sheep (O. dalli dalli), during the last ice age. Here, we used multiple genomes of bighorn and thinhorn sheep, together with snow (O. nivicola) and the domestic sheep (O. aries) as outgroups, to assess their phylogenomic history, potential introgression patterns and their adaptive consequences. Among the Pachyceriforms (snow, bighorn and thinhorn sheep) a consistent monophyletic species tree was retrieved; however, many genealogical discordance patterns were observed. Alternative phylogenies frequently placed Stone and bighorn as sister clades. This relationship occurred more often and was less divergent than that between Dall and bighorn. We also observed many blocks containing introgression signal between Stone and bighorn genomes in which coat colour genes were present. Introgression signals observed between Dall and bighorn were more random and less frequent, and therefore probably due to ILS or intermediary secondary contact. These results strongly suggest that Stone sheep originated from a complex series of events, characterized by multiple, ancient periods of secondary contact with bighorn sheep.
Keywords: gene flow; natural selection; coat color genes; Melanogenesis; adaptive introgression; Ovis ssp